Ambiguitas Semantik dalam Penggunaan 'Konteks' pada Buku Teks Kurikulum Merdeka: Implikasi terhadap Hasil Belajar dan Strategi Pembelajaran - Varary Mechwafanitiara Cantika; Aida Ratna Zulaiha; Widya Puji Astuti; Riche Cynthia Johan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This study examines errors in interpreting the word “konteks” (context) and its equivalents in Merdeka Curriculum textbooks for Indonesian Language, Civic Education, and English Language subjects. Semantic ambiguity and inaccuracies in the use of this term have led to misunderstandings that hinder students' comprehension and learning outcomes. The research aims to identify patterns and potential sources of misinterpretation to ensure alignment between textbook language and the learning objectives of the Merdeka Curriculum. Using a qualitative approach with a comparative method, the study analyzed the meaning and usage of “konteks” across subjects. Data were collected through documentation of both explicit and implicit references, followed by descriptive content analysis based on Miles et al.'s interactive model. Triangulation, expert validation, and adherence to ethical standards ensured the validity and reliability of findings. Results indicate that misinterpretations of “konteks” often lead to fragmented understanding, making it difficult for students to connect concepts across academic and social settings. This disrupts cognitive processes, preventing the development of complex analytical skills. To address these issues, teachers should facilitate clarifying exercises and discussions emphasizing context. Additionally, textbook evaluations must prioritize accurate definitions, precise usage, and illustrative examples to minimize ambiguity and enhance learning outcomes.